Memória Operacional: Modulação pelos processos circadiano e homeostático da regulação sono-vigília - Ginani, Giuliano Emerenciano [UNIFESP] (2014)
The multicomponent model of working memory (MCMWM) proposes a quadripartite system that includes temporary maintenance (visual, spatial and phonological) and manipulation of information (executive functions). It has not been established whether and to what extent the circadian and homeostatic oscillations influence the performance on different subsystems of MCMWM, despite clear evidence of these effects in other cognitive processes. Here we investigate, during 36 hours of continuous wakefulness (from 08:00 to 20:00 the next day), circadian and sleep pressure effects on performance in representative tests of the different subsystems of MCMWM, including measures of working memory capacity (WMC) and executive updating, switching and inhibition . We also evaluate how these subsystems are related to changes in alertness / vigilance, mood, metacognition and intensity identification of six types of facial expressions. Participants were 21 healthy young men with indifferent chronotype. The only MCMWM measures that showed no circadian rhythmicity were the spatial storage and executive shifting. All others exhibited specific rhythms that were not parallel to alert / vigilance / sleepiness except for the visual and phonological storage (maximum 20:00 to 21:00 h; minimum 04:00 to 5:00 h). Only executive inhibition and WMC measures were sensitive to sleep pressure with the worst performance in the morning after the night of extended wakefulness, differing, thus, from the effects of alert / vigilance / sleepiness which became evident during the previous night. Contrary to measure negative affect, subjective ratings of positive affect and attention showed circadian rhythmicity (maximum 09:00 to 10:00 h; minimum 02:00 to 03:00 h) and decreased with increasing time awake, even before night of extended vigilance. This pattern of results were not associated to the MCMWM subsystems and alert / objective attention. Only the identification of disgust faces were affected by extended wakefulness. Reports of cognitive effort involved in tasks not explain the patterns of circadian rhythms, nor the patterns of impairment induced by extended wakefulness. Overall, we found that most of the MCMWM subsystems, WMC and executive domains exhibit circadian rhythmicity, that few are susceptible to extended wakefulness and that these patterns are not similar to the effects of changes in alert / vigilance / sleepiness or subjective evaluations of mood. These results can serve as a guide for selecting appropriate time to assess the MCMWM and has implications for situations that extended wakefulness is involved, such as academic performance, and shift work.